Ajuste de varias ecuaciones de referencia espirométrica a una muestra poblacional en México Adjustment of several spirometric reference equations to a population-based sample in Mexico - Luis Torre-Bouscoulet; Rogelio Pérez-Padilla (Instituto Nacional de Salud Pública, 2006)
OBJETIVOS: Comparar y determinar las ecuaciones de referencia para espirometría que mejor ajustan a una muestra poblacional. MATERIAL Y MÉTODOS: Se compararon los valores espirométricos de 225 sujetos sanos representativos de la población mayor de 40 años de la zona metropolitana de la Ciudad de México, con varias ecuaciones de referencia. El estudio se llevó a cabo entre junio y diciembre de 2003. RESULTADOS: Las ecuaciones que mejor ajustaron para FEV1 y FVC fueron NHANES III para mexicoestadounidenses y para euroestadounidenses, y la del estudio PLATINO. Los valores esperados por Knudson son menores que los observados, y los de Cruz Mérida son mayores. En el análisis del límite inferior de la normalidad, PLATINO fue el más cercano a 5% en el percentil 5. CONCLUSIONES: Mientras se obtienen valores de referencia con una muestra poblacional que cubra un mayor intervalo de edades, las ecuaciones que se recomiendan son NHANES III para mexicoestadounidenses o euroestadounidenses, así como la de PLATINO. OBJETIVE: To compare several forced spirometry reference equations used in Mexico in order to know which of them have a better fit to a population-based sample. MATERIAL AND METHODS: Spirometric values of 225 healthy subjects 40 years of age or older from Metropolitan area of Mexico City, were compared to several reference equations. The sample is population-based and it was done from June to December 2003. The difference between observed and expected values was calculated. A concordance analysis between both observed and expected values was done and the percentage of subjects under normality lower limit was obtained. RESULTS: The equations with better fit for FEV1 and FVC were: NHANES III for Mexican-Americans and Euro-Americans; and from PLATINO. Predicted values according to Knudson were lower, and those from Cruz-Mérida, larger than observed values. Percentage of subjects below lower limit of normal was closest to 5% in the reference values from PLATINO. CONCLUSIONS: We recommend the use of reference values from the study NHANES III (for Mexican-Americans or European-Americans) and PLATINO.